The March of Time: The Cold War 1946-1951, Part 3: Peace or War, 1949-1950 (United States, 1995)
Originally produced as a newsreel by Time Magazine, The March of Time was seen monthly for sixteen years in more than 50,000 theatres around the world. 1. Sweden Looks Ahead. -- Unique among northern European countries, Sweden has been neutral for 135 years. But in uneasy contemporary times the policy of nonpartisanship is difficult to maintain. March of Time captures modern Sweden's carefully constructed society, including fair labor unions, well-run cooperatives and excellent social security. 2. MacArthur's Japan -- Return of the conquering hero! The U.S. occupation, lead by General MacArthur, introduces democratic reforms into the social, political and educational realms of post-war Japan. The U.S. hopes to thereby stem Communism in this defeated Asian country, and teach them to rule themselves. 3. A Chance to Live -- What happened to all the war orphans? In this heartwarming story, we see the history of the Italian Boys' Republic at Santa Marinella. It was established by a kindly priest, but is now run democratically by the boys themselves. The camera follows a boy from his initial distrust of the kindness there to his eventual integration into the community. 4. As Russia Sees It -- Imagine the world situation from the Russian viewpoint. That is what this film does, and, then shows us why they chose Korea for their offensive. It goes on to portray the U.S. meeting of the challenge: reactivating planes, tanks and ships to check the aggression of Stalin and his Communist satellites. 5. The Gathering Storm -- How prepared is America for all-out war? This pictorial analysis gives us a vivid look at just how ready we are for direct attack. Also shown is how much better prepared we are now than we were prior to World War II. This could well be the most dramatic dilemma facing us today -- a communist attack on America!
Duration: 01:25:00
Keywords: Documentary films